MEKANISASI MESIN PENGHANCUR BAWANG SEBAGAI USAHA PENINGKATAN PRODUKTIVITAS RAMBAK - Sutrisna, Sutrisna; Bagus Prasetiyo, Angger; Muhfidin, Rivan; Charlos Basilio Molo, Richardus (Jurnal Pengabdian Masyarakat Polmanbabel, 2024)
The "Lestari" Joint Business Group is a Small and Medium Enterprise in the Rambak business located in Ngolodono, Karangdowo, Klaten, Central Java. This business group makes Rambak with an onion aroma. This community service activity aims to overcome problems and help groups increase Rambak's productivity. From the initial review results, the site service team discovered several issues the "Lestari" Joint Business Group faced. The problem faced by this Joint Business Group is that the implementation process for crushing onions still needs to be simplified and manual. This activity requires a lot of energy and a long time, with the "Lestari" Joint Business Group not having any tools or machines to overcome this problem. Through this Community Service activity, the service team offers innovation in making an onion crusher for the "Lestari" Joint Business Group. Furthermore, the solution is to design and manufacture an effective onion crusher machine that produces more onions.  As a result of this PKM, one unit of onion-crushing equipment was obtained, which will be given to the "Lestari" Joint Business Group located in Ngolodono Karangdowo, Klaten, Central Java.